Intra-Abdominal Desmoplastic Small Round Cell Tumor: Current Treatment Options and Perspectives - Wei, Guixia; Shu, Xinyao; Zhou, Yuwen; Liu, Xia; Chen, Xiaorong; Qiu, Meng (Frontiers in Oncology, 2021)
Intra-abdominal desmoplastic small round cell tumor (IDSRCT) is a rare and highly malignant soft tissue neoplasm, which is characterized by rapid progression and poor prognosis. The mechanism underlying the development of this neoplasm remains elusive, but all cases are characterized by the chromosomal translocation t (11;22) (p13; q12), which results in a formation of EWSR1-WT1 gene fusion. The diagnosis of IDSRCT is often made with core-needle tissue biopsy specimens or laparoscopy or laparotomy. Immunohistochemical analyses have shown the co-expression of epithelial, neuronal, myogenic, and mesenchymal differentiation markers. FISH or reverse transcription polymerase chain reaction detecting EWS-WT1 fusion can be performed to assist in molecular confirmation. There is no standard of care for patients with IDSRCT currently, and majority of newly diagnosed patients received the aggressive therapy, includes >90% resection of surgical debulking, high-dose alkylator-based chemotherapy, and radiotherapy. More recently, targeted therapy has been increasingly administered to recurrent IDSRCT patients and has been associated with improved survival in clinical conditions. Immunotherapy as a possible therapeutic strategy is being explored in patients with IDSRCT. In this review, we summarize currently available knowledge regarding the epidemiology, potential mechanisms, clinical manifestations, diagnosis, treatment, and prognosis of IDSRCT to assist oncologists in comprehensively recognizing and accurately treating this malignancy.